A Composition-Based View of Firm Growth. (16th September 2015) - Luo, Yadong; Child, John
ABSTRACT This article presents a composition-based view (CBV), which explicates the growth of enterprises that compete and develop without the benefit of resource advantages, core technology, or market power. The CBV emphasizes how ordinary firms with ordinary resources may generate extraordinary results through their creative use of open resources and unique integrating capabilities, resulting in an enhanced speed and a price-value ratio that are well suited to large numbers of mass market consumers. In addition to defining the CBV, this article explains the key elements of composition-based strategy and the distinctive processes of composition. Although CBV logic can apply to any firm endeavoring to catch up with better endowed competitors, it aligns well with the case of emerging economy enterprises (EEEs), and Chinese ones in particular. Nonetheless, the advantages of adopting composition-based strategy are temporary in nature and will decline over time, especially after the firm passes the imitative or catch-up stage. We also propose an agenda for future research.